Alternatif Solusi Mengontrol Cahaya Alami pada Desain Bangunan Komersial: Studi Kasus: Toko Busana di Bukit Keminting Palangka Raya - Onie D. Sanitha; Theo Fransisco; Yunida Iashania; Novera Kristianti (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Kristen Duta Wacana Yogyakarta, 2023)
Title: Alternative Solutions to Control Heat Radiation in Commercial Building Design; Case Study: Commercial Buildings In Bukit Keminting, Palangka Raya City A building envelope is a component that protects against environmental influences outside the building that are not expected to be a solution in controlling heat radiation and sunlight. However, the shops in Bukit Keminting, Palangka Raya, have challenges. In addition to its function as a commercial building with essential criteria like visibility aspect, the position of the storefront along the road also directly faces the sunset. This causes the store to receive heat and glare from 2 p.m. to 5 p.m. Using web-based software development from AndrewMarsh.com. This study focuses on effective shading devices for stores in Bukit Keminting Palangka Raya in controlling heat radiation without eliminating the vital aspect of visibility for commercial buildings. The software analysis shows that a highly flexible device is the most suitable solution. The type of shading device with these properties is the type of external Venetian blind, which can be adjusted according to the direction of the incoming light, which changes every month.